Implementasi Gerakan Literasi Sekolah Untuk Meningkatkan Minat Baca Siswa di Sekolah Dasar 060857 Medan Tembung - Mutiara Gultom; Sri Lewi Giovani Lubis; Syahrial Syahrial; Viladelvia Viladelvia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Reading literacy is not just an ordinary reading activity but an activity that can build culture itself. Literacy activities do refer to a person's basic ability to read and write. So far, the strategy carried out to improve this ability is to foster interest in reading and writing. Through reading is the same as grasping the whole world, because in reading can access information from all over the world.Increased literacy will lead to higher literacy Optimizing human resources, especially in fulfilling 21st century skills and the formation of good citizens. Unfortunately, the existence of the library today has not been able to inspire students to read even just for visiting. The use of reading corners in the classroom is a very effective solution to improve reading culture and explain the importance of literacy in today's digital era. This is the purpose of this study.This research uses a qualitative approach and a phenomenological type of study research. The method of determining the subject uses purpossive and snowball. User data collection methods using observation, interviews and documentation, and data analysis using interactive models.